2013
DOI: 10.1302/0301-620x.95b8.31377
|View full text |Cite
|
Sign up to set email alerts
|

Serial magnetic resonance imaging of metal-on-metal total hip replacements

Abstract: Metal artefact reduction (MAR) MRI is now widely considered to be the standard for imaging metal-on-metal (MoM) hip implants. The Medicines and Healthcare Products Regulatory Agency (MHRA) has recommended cross-sectional imaging for all patients with symptomatic MoM bearings. This paper describes the natural history of MoM disease in a 28 mm MoM total hip replacement (THR) using MAR MRI. Inclusion criteria were patients with MoM THRs who had not been revised and had at least two serial MAR MRI scans. All exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 26 publications
2
40
1
Order By: Relevance
“…5,15 However, the natural history of ARMD is not well understood. 36,37 Decisions relating to revision surgery must therefore be considered on a case-by-case basis. This should include thorough discussion with the patient about the potential risks of further surveillance as well as risks associated with revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5,15 However, the natural history of ARMD is not well understood. 36,37 Decisions relating to revision surgery must therefore be considered on a case-by-case basis. This should include thorough discussion with the patient about the potential risks of further surveillance as well as risks associated with revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a lack of knowledge about when and how rapidly pseudotumours develop, as all but two crosssectional imaging studies on pseudotumours have been retrospective in design, with only one follow-up. 5,6,13,[14][15][16][17][18] Almousa et al 19 recently described the natural history of ten pseudotumours in asymptomatic patients using ultrasound examination, and observed both an increase (n = 6) in size of the pseudotumour, a decrease in size (n = 1), and the disappearance of pseudotumours (n = 3). However, we do not know whether and when new pseudotumours are detected with repeated cross-sectional imaging in MoM hip resurfacing, or the natural history of small asymptomatic pseudotumours.…”
mentioning
confidence: 99%
“…Lastly, none of the studies reported have a true gold standard for comparing imaging study results with intraoperative, histologic specimens, because the presence or absence of false-negatives based on imaging studies cannot be confirmed. Imaging surveillance mechanisms to detect wear-related corrosion problems after hip arthroplasty are crucial, because the majority of studies demonstrate that adverse local tissue reactions can present in asymptomatic patients with well-fixed, well-aligned components, and no consistent association has been established between serum metal ion content and the presence of a soft tissue reaction [2,6,8,11,12,17,24,32,33]. The accessibility and low cost of US make it an attractive surveillance mechanism after MoM THAs and SRAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, disadvantages include the cost associated with its use along with differences in the accessibility of specific sequencing protocols at different institutions. MRI with or without MARS has been the most commonly reported surveillance mechanism for the presence of wear-related corrosion problems in hip arthroplasty [8,11,12,16,17,[28][29][30]. The use of specific, metal artifact reduction sequences such as MAVRIC (multiple acquisition variable-resonance image combination) and SEMAC (slice encoding for metal artifact correction) has increased the ability to both identify and characterize these soft tissue lesions [18,20,25].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%